2003
DOI: 10.1038/sj.bjc.6601011
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to gemcitabine of P-glycoprotein and multidrug resistance-associated protein-overexpressing human cancer cell lines

Abstract: Gemcitabine (2 0 ,2 0 -difluorodeoxycytidine) is a deoxycytidine analogue that is activated by deoxycytidine kinase (dCK) to its monophosphate and subsequently to its triphosphate dFdCTP, which is incorporated into both RNA and DNA, leading to DNA damage. Multidrug resistance (MDR) is characterised by an overexpression of the membrane efflux pumps P-glycoprotein (P-gP) or multidrug resistance-associated protein (MRP). Gemcitabine was tested against human melanoma, non-small-cell lung cancer, smallcell lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
94
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 47 publications
5
94
1
1
Order By: Relevance
“…Cepharanthine reversed gemcitabine resistance in A549/GR cells. Although cepharanthine has been also reported to be an inhibitor of the P-gp efflux pump (16), NSCLC cell lines transfected with MDR1 gene had augmented sensitivity to gemcitabine (17). These findings suggest that cepharanthine might be effective in restoring the sensitivity of tumors to gemcitabine by inhibiting the drug efflux activity of MRP7 but not P-gp.…”
Section: Discussionmentioning
confidence: 57%
“…Cepharanthine reversed gemcitabine resistance in A549/GR cells. Although cepharanthine has been also reported to be an inhibitor of the P-gp efflux pump (16), NSCLC cell lines transfected with MDR1 gene had augmented sensitivity to gemcitabine (17). These findings suggest that cepharanthine might be effective in restoring the sensitivity of tumors to gemcitabine by inhibiting the drug efflux activity of MRP7 but not P-gp.…”
Section: Discussionmentioning
confidence: 57%
“…Gemcitabine is a novel nucleoside analogue, which is active in solid tumours such as pancreatic, ovarian and non-small cell lung cancer (Burris et al, 1997;Manegold et al, 1997). In vitro studies of gemcitabine have demonstrated its ability to circumvent multi-drug resistance (MDR) secondary to increased P-glycoprotein and MDR protein 1 overexpression (Bergman et al, 2003). These MDR cells are associated with increased deoxycytidine kinase activity and reduced deoxycytidine deaminase activity leading to accumulation and increase sensitivity to gemcitabine (Bergman et al, 2001).…”
mentioning
confidence: 99%
“…Among more recent chemotherapeutic agents, gemcitabine appears to be the most promising drug available, in part because it is not a known substrate for P-glycoprotein, 24 which is responsible for the well known chemoresistance of RCC. 25 Recently, the combination of gemcitabine and 5-FU proved to be active against RCC, 14 but no further improvements were recorded when either cisplatin, 19 interferon, or IL-2 18 was added; furthermore, a Phase II study of gemcitabine, 5-FU, and oral thalidomide resulted in an unacceptably high incidence of thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%